IMPLEMENTATION OF USER INTERFACE AND USER EXPERIENCE CAR WASH SERVICE PROVIDER ANDROID BASED APPLICATION “SPOTLESS” USING DESIGN THINKING METHOD - Diva Kurnia Achmadi; Swahesti Puspita Rahayu; Yogiek Indra Kurniawan (Jurnal Teknik Informatika (Jutif), 2022)
"SPOTLESS" is an Android-based mobile application that provides car wash services to assist customers in ordering car wash appointments and vehicle wash pick-up services at the customer's desired place. "SPOTLESS" can be a solution for car users to avoid long queues for car washing or the lack of time to take their car directly to the washroom. The increasing demand for vehicle washing services affects business competition in this business, causing many customers to complain because they have to wait in queues for too long, disrupting customers' routine activities. To improve customer satisfaction, the interface is designed using the design thinking method, which was tested using the eye-tracking method through 5 participants to determine the feasibility level from the user's side After 3 iterations of testing using Maze, we got a usability score of 86 which is included in the high usability category.